Libri elettronici: Pratiche della didattica e della ricerca Electronic Books: Teaching and Research Practices - Roberto Delle Donne (Saperi storici e nuove tecnologie, 2005)
This proceedings e-book contains papers presented at the national Symposium on "Electronic Books and the practices of scholarly research", held in Naples, Italy, on 20 June 2003. The advent of new technologies, tools, and digital resources is changing how scholars conduct their work, keep updated in their field or fields of study, and think about research. Moving from the reconstruction of the market of scientific communication, copyright policies, and management of long-term conservation strategies, the published papers aim to discuss the ways in which scholarly practices have changed in the last decades, even since the end of the last century, in teaching and in research, in various disciplines like history, phisics and biomedical sciences.